Gratitude Moderates the Mediating Effect of Deliberate Rumination on the Relationship Between Intrusive Rumination and Post-traumatic Growth - Kim, Eunseung; Bae, Sungman (Frontiers in Psychology, 2019)
Purpose: This study aimed to examine the moderating effect of gratitude on the mediating effect of deliberate rumination on the relationship between intrusive rumination and posttraumatic growth. Methods: We used self-report questionnaires to collect data from 450 18–68-year-old participants (Mage = 39.73, SD = 13.73) who were residing in major cities and regions across South Korea. Data that were collected from 411 participants were subjected to analysis. Version 25 of SPSS(Statistical Package for Social Science) and PROCESS macro were used to analyze mediation, moderation, and moderated mediation effects. Results: Deliberate rumination mediated the relationship between intrusive rumination and posttraumatic growth. Gratitude moderated the effect of deliberate rumination on posttraumatic growth. Finally, gratitude moderated the mediating effect of deliberate rumination on the relationship between intrusive rumination and posttraumatic growth. Conclusion: Deliberate rumination and gratitude facilitate posttraumatic growth among traumatized adults. In particular, gratitude reinforces the effect of deliberate rumination on posttraumatic growth.